Assessing Asymmetry In Collegiate Sprint And Intermediate Hurdlers - Gregory, Robert; Dale, Hunter (Medicine & Science in Sports & Exercise, 2025)
Keywords: Asymmetry; Ground reaction force; Impulse (physics); Jump; Plyometrics; Sprint; dept.hms

Concurrent validation of the tandem walk test as a measure of dynamic walking balance in a healthy population - Robertson, Marc; Gregory, Robert (Physical Therapy and Rehabilitation, 2017)
4 citations (Crossref) [2023-10-31] Citation Key Alias: robertsonConcurrentValidationTandem2017a
Keywords: dept.hms; peer-reviewed

Effect of age on dynamic walking balance in a healthy population between the ages of 20 and 80 years - Robertson, Marc; Gregory, Robert (Physical Therapy and Rehabilitation, 2018)
2 citations (Crossref) [2023-10-31] Citation Key Alias: robertsonEffectAgeDynamic2018a
Keywords: dept.hms; peer-reviewed

Establishing a global standard for wearable devices in sport and fitness: Perspectives from the new england chapter of the american college of sports medicine members. - Ash, Garrett I.; Stults-Kolehmainen, Matthew A.; Busa, Michael A.; Gregory, Robert; Garber, Carol Ewing; Liu, Jason; Gerstein, Mark; Casajús, José A.; González-Agüero, A.; Constantinou, Demitri; Geistlinger, Michael; Guppy, Fergus M.; et al. (Current sports medicine reports, 2020)
The recent explosion of wearable technology and the associated concerns prompted the International Federation of Sports Medicine (FIMS) to create a quality assurance standard for wearable devices, which provides commissioned testing of marketing claims and endorsement of commercial wearables that test favorably. An open forum as announced in the conference advertising was held at the Annual Meeting of the New England Regional Chapter of the American College of Sports Medicine (NEACSM) November 7 to 8, 2019, in Providence, Rhode Island, USA for attending NEACSM members to voice their input on the process. Herein, we report the proceedings. The round table participants perceived the quality assurance standard to be important, but identified some practical process challenges that included the broad scope and complexity of the device universe, the need for a multiphase testing pathway, and the associated fees for product evaluation. The participants also supported the evaluation of device data analysis, behavioral influences, and user experience in the overall evaluation. Looking forward, the FIMS quality assurance standard faces the challenge of balancing these broader perspectives with practical constraints of budget, facilities, time, and human resources. © 2020 by the American College of Sports Medicine.
14 citations (Crossref) [2023-10-31] tex.ids: ashEstablishingGlobalStandard2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85079081076 type: Article
Keywords: Fitness Trackers; Humans; New England; Sports; Sports Medicine; United States; Wearable Electronic Devices; activity tracker; adult; article; budget; cosmos; data analysis; dept.hms; electronic device; human; peer-reviewed; quality control; sport; sports medicine

Establishing a global standard for wearable devices in sport and exercise medicine: Perspectives from academic and industry stakeholders - Ash, Garrett I.; Stults-Kolehmainen, Matthew; Busa, Michael A.; Gaffey, Allison E.; Angeloudis, Konstantinos; Muniz-Pardos, Borja; Gregory, Robert; Huggins, Robert A.; Redeker, Nancy S.; Weinzimer, Stuart A.; Grieco, Lauren A.; Lyden, Kate; et al. (Sports medicine (Auckland, N.Z.), 2021)
Millions of consumer sport and fitness wearables (CSFWs) are used worldwide, and millions of datapoints are generated by each device. Moreover, these numbers are rapidly growing, and they contain a heterogeneity of devices, data types, and contexts for data collection. Companies and consumers would benefit from guiding standards on device quality and data formats. To address this growing need, we convened a virtual panel of industry and academic stakeholders, and this manuscript summarizes the outcomes of the discussion. Our objectives were to identify (1) key facilitators of and barriers to participation by CSFW manufacturers in guiding standards and (2) stakeholder priorities. The venues were the Yale Center for Biomedical Data Science Digital Health Monthly Seminar Series (62 participants) and the New England Chapter of the American College of Sports Medicine Annual Meeting (59 participants). In the discussion, stakeholders outlined both facilitators of (e.g., commercial return on investment in device quality, lucrative research partnerships, and transparent and multilevel evaluation of device quality) and barriers (e.g., competitive advantage conflict, lack of flexibility in previously developed devices) to participation in guiding standards. There was general agreement to adopt Keadle et al.’s standard pathway for testing devices (i.e., benchtop, laboratory, field-based, implementation) without consensus on the prioritization of these steps. Overall, there was enthusiasm not to add prescriptive or regulatory steps, but instead create a networking hub that connects companies to consumers and researchers for flexible guidance navigating the heterogeneity, multi-tiered development, dynamicity, and nebulousness of the CSFW field. © 2021, The Author(s), under exclusive licence to Springer Nature Switzerland AG.
9 citations (Crossref) [2023-10-31] https://waseda.pure.elsevier.com/en/publications/establishing-a-global-standard-for-wearable-devices-in-sport-and- ; https://repository.up.ac.za/handle/2263/81930?show=full ; https://www.ncbi.nlm.nih.gov/pubmed/34468950 ; https://researchportal.northumbria.ac.uk/en/publications/establishing-a-global-standard-for-wearable-devices-in-sport-and- ; https://pubmed.ncbi.nlm.nih.gov/34468950/ ; https://link.springer.com/article/10.1007/s40279-021-01543-5
Keywords: Consensus; Exercise; Humans; Sports; Sports Medicine; United States; Wearable Electronic Devices; adult; article; consensus; consumer; data science; dept.hms; electronic device; exercise; female; human; human experiment; investment; major clinical study; male; sport; sports medicine